Cystic Optic Chiasm Lesion: Atypical Magnetic Resonance Imaging Findings. (4th July 2017) - Haque, Sameen; Reid, Kate; O'Neil, Ross; Lueck, Christian
ABSTRACT: Intrinsic cystic lesions in the optic chiasm are an uncommon cause of bitemporal hemianopia compared with compressive lesions extrinsic to the chiasm. A 40-year-old man presented with difficulty driving. Clinical assessment revealed a bitemporal hemianopia. Magnetic resonance imaging showed an unusual cystic appearance of the chiasm. The appearance was felt to be most likely secondary to previous infective or inflammatory disease, but biopsy was not undertaken given the very significant risk of further visual loss.